Application of a modified multifunctional short peptide in the treatment of periodontitis - Xi Zhang; Meiyan Song; Hongbo Wang; Qian Zhang; Zhiyang Liu; Jiayin Deng (Scientific Reports)
Abstract Periodontitis is a chronic inflammatory disease involving plaque biofilm as a pathogenic factor. Potassium ion plays an important role in cellular homeostasis; a large outflow of potassium may lead to local inflammation progression. In this work, the multifunctional short peptide molecule BmKTX-33 was designed by modifying the BmKTX, a Kv1.3 potassium channel inhibitor. This was to explore its antibacterial properties, capability of maintaining cell ion homeostasis, and bone-forming capacity. The results showed that BmKTX-33 had inhibitory effects on S. gordonii, F. nucleatum, and P. gingivalis. Moreover, BmKTX-33 also inhibited excessive potassium outflow in inflammatory environments. Finally, BmKTX-33 promoted MC3T3-E1 early osteogenesis while suppressing the NLRP3 inflammasome's production. In conclusion, BmKTX-33 not only has antibacterial properties, but also can inhibit the expression of NLRP3 inflammasome and play an anti-inflammatory role.